The dog, Ray - Coggin, Linda (Candlewick Press, 2018)
Twelve-year-old Daisy Fellows' death was swift and unexpected. When she finds herself standing in an otherworldly Job Center where she's instructed to select a new role for her soul to step into, she accidentally goes through the wrong door and finds her soul born into the body of a puppy. Determined to find her grieving parents, Daisy, now a dog, runs away. But when she meets a runaway boy named Pip who is searching for his father, she finds her loyalty shifting from her parents to Pip as her soul settles into its new purpose.